Awakening ancient polar Actinobacteria: diversity, evolution and specialized metabolite potential. Issue 11 (8th October 2019) - Millán-Aguiñaga, Natalie; Soldatou, Sylvia; Brozio, Sarah; Munnoch, John T.; Howe, John; Hoskisson, Paul A.; Duncan, Katherine R.
Abstract : Polar and subpolar ecosystems are highly vulnerable to global climate change with consequences for biodiversity and community composition. Bacteria are directly impacted by future environmental change and it is therefore essential to have a better understanding of microbial communities in fluctuating ecosystems. Exploration of Polar environments, specifically sediments, represents an exciting opportunity to uncover bacterial and chemical diversity and link this to ecosystem and evolutionary parameters. In terms of specialized metabolite production, the bacterial order Actinomycetales, within the phylum Actinobacteria are unsurpassed, producing 10 000 specialized metabolites accounting for over 45 % of all bioactive microbial metabolites. A selective isolation approach focused on spore-forming Actinobacteria of 12 sediment cores from the Antarctic and sub-Arctic generated a culture collection of 50 strains. This consisted of 39 strains belonging to rare A ﻿ctinomycetales genera including Microbacterium, Rhodococcus and Pseudonocardia . This study used a combination of nanopore sequencing and molecular networking to explore the community composition, culturable bacterial diversity, evolutionary relatedness and specialized metabolite potential of these strains. Metagenomic analyses using MinION sequencing was able to detect the phylum Actinobacteria across polar sediment cores at an average of 13 % of the total bacterial reads. The resulting molecular network consisted of 1652 parent ions and the lack of known metabolite identification supports the argument that Polar bacteria are likely to produce previously unreported chemistry.